2004
DOI: 10.1248/bpb.27.768
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aminopeptidases in the Blood Pressure Regulation

Abstract: In addition to the neural and autoregulatory factors, blood pressure (BP) is regulated by humoral factors including vasoactive peptides. When evaluating the peptide actions, degradation by proteases should be also considered in addition to the generation of peptides and their receptors. This review describes the roles of aminopeptidase A, placental leucine aminopeptidase and kininase I, which are enzymes responsible for hydrolyzing angiotensin II (AngII), vasopressin (AVP) and bradykinin (BK), respectively, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…This result would support the possibility that the cleavage of N-terminal Arg residues catalyzed by AP-O could also be of in vivo relevance. This possibility, together with the expression of the AP-O gene in the heart and testis, tissues in which the renin-angiotensin system plays important roles (5,69), prompted us to investigate the putative involvement of AP-O in the processing of peptides of this system. The renin-angiotensin system regulates the homeostasis, blood pressure, endocrine processes, and behavior at the systemic level as well as at the local tissue level (5,69).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result would support the possibility that the cleavage of N-terminal Arg residues catalyzed by AP-O could also be of in vivo relevance. This possibility, together with the expression of the AP-O gene in the heart and testis, tissues in which the renin-angiotensin system plays important roles (5,69), prompted us to investigate the putative involvement of AP-O in the processing of peptides of this system. The renin-angiotensin system regulates the homeostasis, blood pressure, endocrine processes, and behavior at the systemic level as well as at the local tissue level (5,69).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are widely distributed in multiple organisms from bacteria to human and play essential roles in protein maturation and regulation of the metabolism of bioactive peptides (1,2). Furthermore, alterations in the function and regulation of aminopeptidases underlie several human diseases, including cancer and cardiovascular disorders (3)(4)(5). Among the different families of human aminopeptidases, there has been a growing interest in the analysis of the biological and pathological relevance of members of the M1 family of zinc metallopeptidases or gluzincins (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II is a cytokine that participates in renal damage and has vasoactive and profibrotic properties and contributes to kidney injury by causing hypertension and glomerulosclerosis. Impairment of Ang II degradation may influence Ang II action and, indeed, animal studies have suggested a role for APA in blood pressure regulation (Mitsui et al 2003(Mitsui et al ,2004. All components of the RAS are highly expressed in the developing kidney.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the M1 aminopeptidases play important roles in the metabolism of vasoactive peptide hormones, such as angiotensins and kallidin in the placenta (39). In brief, APA degrades angiotensin II to angiotensin III, and then APN, P-LAP, and LVRN/APQ can generate angiotensin IV from angiotensin III and bradykinin from kallidin.…”
Section: Discussionmentioning
confidence: 99%